Association between estimated glucose disposal rate and metabolic syndrome: a cross-sectional analysis of the National Health and Nutrition Examination Survey - Xia, Kaide; Jin, Shuai; Chen, Guifang; Zhang, Haiwang; Zhang, Qiao (Frontiers in Nutrition, 2025)
Metabolic syndrome (MS) is a complex metabolic disorder that is often closely associated with the development of chronic diseases such as cardiovascular disease and diabetes. This study aimed to explore the relationship between estimated glucose metabolic rate (eGDR) and MS. The correlation between eGDR levels and the prevalence of metabolic syndrome was analyzed here based on data from the National Health and Nutrition Examination Survey from 2005 to 2020. The study sample consisted of 63,131 adult participants, and the results showed that lower eGDR levels were significantly associated with a higher prevalence of metabolic syndrome. Further regression analyses showed that eGDR acted as a protective factor and that the risk of MS significantly decreased as its level increased. Subgroup analyses showed that this trend held across gender, age, and BMI categories, and that the protective effect of eGDR was weaker in the higher BMI group. Based on the nonlinear relationship between subjects’ eGDR levels and MS prevalence, RCS analyses further confirmed a significant correlation between lower eGDR levels and increased risk of MS. In conclusion, the present study suggests that eGDR levels could serve as a potential biomarker for predicting metabolic syndrome, providing new perspectives for early screening and intervention of MS.